2020
DOI: 10.1055/a-1134-4873
|View full text |Cite
|
Sign up to set email alerts
|

Use of ERCP in the United States over the past decade

Abstract: Background and study aims With newer imaging modalities, indications for use of endoscopic retrograde cholangiopancreatography (ERCP) have changed in the last decade. Despite advances in ERCP, paucity in recent literature regarding utilization and outcomes of ERCP exists. Thus, the aim of this study was to assess the inpatient use of ERCP, outcomes, and most common indications. Patients and methods Retrospective-cohort study using the Nationwide Inpatient Sample 2007–2016. All patients with ICD9–10CM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 36 publications
2
28
0
Order By: Relevance
“…Though ERCP in 2020 is primarily a therapeutic procedure, with minimal diagnostic indications, it remains one of the most commonly performed endoscopic procedures in the USA and world-wide, with volumes having increased over time. 5 6 Even though ERCP is a relatively safe procedure overall, AEs are more prevalent with its performance than any other endoscopic procedure. Thus, it behoves endoscopists performing ERCP to be acutely aware of the most precise and up-to-date estimates of risk possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though ERCP in 2020 is primarily a therapeutic procedure, with minimal diagnostic indications, it remains one of the most commonly performed endoscopic procedures in the USA and world-wide, with volumes having increased over time. 5 6 Even though ERCP is a relatively safe procedure overall, AEs are more prevalent with its performance than any other endoscopic procedure. Thus, it behoves endoscopists performing ERCP to be acutely aware of the most precise and up-to-date estimates of risk possible.…”
Section: Discussionmentioning
confidence: 99%
“… 1–4 Although the role of standard ERCP has transitioned to that of a primarily therapeutic procedure, ERCP volumes have nevertheless risen over the past 10–15 years in the USA. 5 6 ERCP is performed across high-volume and low-volume centres, and by endoscopists of variable experience and specialties. 7 A steep learning curve during a specialised period of training results in an advanced skill set required to perform safe and effective ERCP.…”
Section: Introductionmentioning
confidence: 99%
“…The main indication for ERCP is choledocholithiasis[ 49 ] which can cause cholangitis, biliary obstruction, and pancreatitis. For routine stones < 1 cm, a sphincterotomy with stone extraction using a balloon or basket is performed.…”
Section: Ercp and Its Role In The Diagnosis And Management Of Biliary Diseasementioning
confidence: 99%
“…ERCP is now routinely used for the management of numerous benign and malignant pancreatobiliary diseases [2][3][4]. A recent report suggested that while the use of ERCP in the United States increased over the past decade, there has also been an increase in ERCP-related adverse events (AEs) [5].…”
Section: Introductionmentioning
confidence: 99%